Continuous finite- and fixed-time high-order regulators - Basin, Michael; Shtessel, Yuri; Aldukali, Fathi (Journal of the Franklin Institute, 2016)
The contribution of this paper is twofold. First, an upper estimate of the convergence (settling) time is calculated for the finite-time convergent control algorithm that drives the state of a series of integrators to the origin. To the best of our knowledge, such an estimate is obtained for the first time. Second, a novel fixed-time continuous control law is proposed for a chain of integrators of an arbitrary dimension. Its fixed-time convergence is established and the uniform upper bound of the settling time is computed. The theoretical developments are applied to a case study of controlling a DC motor.